Atopic dermatitis: Role of the skin barrier, environment, microbiome, and therapeutic agents. Issue 3 (June 2021) - Luger, Thomas; Amagai, Masayuki; Dreno, Brigitte; Dagnelie, Marie-Ange; Liao, Wilson; Kabashima, Kenji; Schikowski, Tamara; Proksch, Ehrhardt; Elias, Peter M.; Simon, Michel; Simpson, Eric; Grinich, Erin; et al.
Highlights: Impaired skin barrier function drives the pathophysiology of atopic dermatitis. Defects in skin barrier component genes lead to impaired skin barrier function. Environmental factors may worsen atopic dermatitis through cutaneous exposure. The cutaneous microbiome is an important component of the skin barrier function. Several therapies for atopic dermatitis promote restoration of the skin barrier. Abstract: Atopic dermatitis (AD) is a chronic, inflammatory skin disorder characterized by eczematous and pruritic skin lesions. In recent decades, the prevalence of AD has increased worldwide, most notably in developing countries. The enormous progress in our understanding of the complex composition and functions of the epidermal barrier allows for a deeper appreciation of the active role that the skin barrier plays in the initiation and maintenance of skin inflammation. The epidermis forms a physical, chemical, immunological, neuro-sensory, and microbial barrier between the internal and external environment. Not only lesional, but also non-lesional areas of AD skin display many morphological, biochemical and functional differences compared with healthy skin. Supporting this notion, genetic defects affecting structural proteins of the skin barrier, including filaggrin, contribute to an increased risk of AD. There is evidence to suggest that natural environmental allergens and man-made pollutants are associated with an increased likelihood of developing AD. A compromised epidermal barrier predisposes the skin to increased permeability of these compounds. Numerous topical and systemic therapies for AD are currently available or in development; while anti-inflammatory therapy is central to the treatment of AD, some existing and novel therapies also appear to exert beneficial effects on skin barrier function. Further research on the skin barrier, particularly addressing epidermal differentiation and inflammation, lipid metabolism, and the role of bacterial communities for skin barrier function, will likely expand our understanding of the complex etiology of AD and lead to identification of novel targets and the development of new therapies.